Effectiveness of 8 weeks of Panchakshari mantra chanting on cognitive and psychological parameters in young adults - Anitha Lakshmi; Bhargavi SK; Shashikumar SD; Yashica Gowda R; Sai Sailesh Kumar Goothy; Mukkadan JK (Asian Journal of Medical Sciences, 2024)
Background: It was reported that those who practice chanting of the Shiva panchakshari mantra can overcome stress, attain prosperity, and get stability in life. However, there are no research studies in this area in the PubMed literature to support scientific evidence. Aims and Objectives: The present study was undertaken to observe the effectiveness of 8 weeks of Panchakshari mantra chanting on cognitive and psychological parameters in young adults. Materials and Methods: A total of 60 young adults were part of the study after obtaining the written informed consent. After recruiting, they were randomly assigned to two groups, control and experimental groups with 30 participants in each group. After recording the baseline, the participants in the experimental group were trained in chanting the panchakshari mantra for a week under the supervision of Vedic teachers. The participants in the control group were not allowed to chant during the study period. All the parameters were recorded in both groups after 8 weeks of the intervention. Results: There was a significant decrease in the depression, anxiety, and stress scores of the participants of the experimental group after the intervention. There was a significant improvement in the scores of spatial and verbal memory in the participants of the experimental group followed by the intervention. Conclusion: There was a significant improvement in the verbal memory scores in the participants of the experimental group. There was a significant decrease in the depression, anxiety, and stress scores of the participants followed by the chanting. The study recommends further detailed studies in this area to provide further scientific evidence.